Fungitoxic action of fungicides on the germination of Puccinia hemerocallidis urediniospores (Revista de Ciências Agroveterinárias, 2014)
The daylily rust culture, caused by Puccinia hemerocallidis, is a major foliar disease. The application of fungicide is the method of control of this disease, however, in Brazil there are little recent studies evaluating the control of this pathogen. The objective was to determine the inhibitory concentration (IC50 and IC100) of eight products on the germination the P. hemerocallidis urediniospores. Fungicides azoxystrobin, picoxystrobin, pyraclostrobin, trifloxystrobin, cyproconazole, epoxiconazole and tebuconazole were tested; in addition to the rock dust, all at concentrations of 0, 0.01, 0.1, 1, 10 and 100 mg L-1. The products were diluted successively to obtain the desired concentrations, mixed in water-agar media and after solidifying the mixture was added to Petri dishes along with the suspension of urediniospores. The experimental design was completely randomized with four replications. Under the optical microscope 100 urediniospores per Petri dish were analyzed. Data was statistically analyzed by regression. All fungicides from the strobilurin chemical group (azoxystrobin, picoxystrobin, pyraclostrobin and trifloxystrobin) and tebuconazole showed highly toxicity to urediniospores of the P. hemerocallidis, and epoxiconazole and cyproconazole fungicides, such as the rock dust had moderately toxicity.
Keywords: Daylily rust; Fungicides; Rock dust; Inhibitory concentration.